The influence of Service Quality on Customer Satisfaction at Workshop PT Wahana Sun Motor Branch Puri Anjasmoro - Diaz - Ardiani; Noor - Suroija; Eva - Purnamasari (Politeknik Negeri Semarang, 2020)
This study aimed to determine the influence of service quality on customer satisfaction at workshop PT Wahana Sun Motor Branch Office Puri Anjasmoro. This research used the dimensions of service quality, namely : tangible, reliability, responsiveness, assurance, and empathy to customer satisfaction. Data analysis that used were instrument test, classical assumption test, multiple linear regression analysis, and hypothesis test. The sample that used in this study were 100 respondents that choosen using probability sampling method. Hypothesis test result indicate that tangible, reliability, responsiveness, assurance, and empathy influencing the customer satisfaction. Furthermore, tangible, reliability, responsiveness, assurance, and empathy simultaneously influencing the customer satisfaction. The results of the coefficient of determination indicate that tangible, reliability, responsiveness, assurance, and empathy influencing the customer satisfaction by 60,3% and the remaining 39,7% of customer satisfaction is influenced by other factors which were not observed in this study